Factors influencing diagnosis and treatment of osteoporosis after a fragility fracture among postmenopausal women in Asian countries: A retrospective study - Annie W. Kung (2018)
Background: A vast amount of literature describes the incidence of fracture as a risk for recurrent osteoporotic fractures in western and Asian countries. Osteoporosis evaluation and treatment after a low-trauma fracture, however, has not been well characterized in postmenopausal women in Asia. The purpose of this study was to characterize patient and health system characteristics associated with the diagnosis and management of osteoporosis among postmenopausal women hospitalized with a fragility fracture in Asia.Methods: Patient surveys and medical charts of postmenopausal women (N=1,122) discharged after a fragility hip fracture from treatment centers in mainland China, Hong Kong, Singapore, South Korea, Malaysia, Taiwan, and Thailand between July 1, 2006 and June 30, 2007 were reviewed for bone mineral density (BMD) measurement, osteoporosis diagnosis, and osteoporosis treatment.Results: The mean (SD) age was 72.9 (11.5) years. A BMD measurement was reported by 28.2% of patients, 51.5% were informed that they had osteoporosis, and 33.0% received prescription medications for osteoporosis in the 6 months after discharge. Using multivariate logistic regression analyses, prior history of fracture decreased the odds of a BMD measurement (OR 0.63, 95% CI 0.45-0.88). Having a BMD measurement increased the odds of osteoporosis diagnosis (OR 10.1, 95% CI 6.36-16.0), as did having health insurance (OR 4.95, 95% CI 1.51-16.21 for private insurance with partial self-payment relative to 100% self-payment). A history of fracture was not independently associated with an osteoporosis diagnosis (OR 0.80, 95% CI 0.56-1.15). Younger age reduced the odds of receiving medication for osteoporosis (OR 0.59, 95% CI 0.36-0.96 relative to age ≥65), while having a BMD measurement increased the odds (OR 1.79, 95% CI 1.23-2.61).Conclusions: Osteoporosis diagnosis and treatment in Asian countries were driven by BMD measurement but not by fracture history. Future efforts should emphasize education of general practitioners and patients about the importance of fracture. © 2013 Kung et al; licensee BioMed Central Ltd.